Augmented reality technology and possibilities of its use in teaching computer science to junior schoolchildren - Yulia E. Zenkina (RUDN Journal of Informatization in Education)
Problem statement. In the paper, the author sets a goal to identify the potential of educational technology of augmented reality in the process of teaching computer science to junior schoolchildren using the example of 4th grade students. Methodology. The article analyzes educational and methodological literature, as well as scientific articles by teachers and scientists who propose the use of augmented reality technology in the educational process. The advantages and disadvantages of this technology are identified, and its capabilities in improving the quality of teaching the subject, developing students’ logical thinking, and forming a sustainable motivation to study the subject under consideration are demonstrated. It is concluded that there are insufficient approaches to teaching computer science using augmented reality technology for primary school students. Results. The experiment showed the effectiveness of using augmented reality technology in computer science lessons in primary school. The author of the article argues, that augmented reality technology makes it possible to introduce elements of entertainment and interactivity into the learning process, as well as gamify the process of transmitting knowledge that has a positive impact on the development of cognitive interest of younger schoolchildren in mastering both computer science and mathematics, with which the study of computer capabilities is successfully integrated. Conclusion. The paper outlines several recommendations that make it possible to qualitatively include augmented reality technologies in the process of teaching computer science to junior schoolchildren, designed to diversify the course of teaching the subject under consideration.